Medial percutaneous hemi-epiphysiodesis improves the valgus tilt of the femoral head in developmental dysplasia of the hip (DDH) type-II avascular necrosis. (2015) - Agus, Haluk; Önvural, Burak; Kazimoglu, Cemal; Reisoglu, Ali; Kalenderer, Onder
<x xml:space="preserve">Abstract</x> Background and purpose — Avascular necrosis (AVN) is a major cause of disability after treatment of developmental dysplasia of the hip (DDH), leading to femoral head deformity, acetabular dysplasia, and osteoarthritis in adult life. Type-II AVN is characterized by retarded growth in the lateral aspect of the physis or by premature lateral fusion, which produces a valgus deformity of the head on the neck of the femur. We investigated the effect of medial percutaneous hemi-epiphysiodesis as a novel technique in the treatment of late-diagnosed type-II AVN. Patients and methods — 9 patients (11 hips) with a diagnosis of type-II AVN who underwent medial percutaneous hemi-epiphysiodesis after the surgical treatment for DDH were included in the study. 10 patients (12 hips) with the same diagnosis but who did not undergo hemi-epiphysodesis were chosen as a control group. Preoperative and postoperative articulotrochanteric distances, head-shaft angles, CE (center-edge) angles, and physeal inclination angles were measured. The treatment group underwent medial hemi-epiphysodesis at a mean age of 8 years. The mean ages of the treatment group and the control group at final follow-up were 14 and 12 years respectively. The mean duration of follow-up was 5.7 years in the treatment group and 8.3 years in the control group. Results — Preoperative articulotrochanteric distance, head-shaft angle, and functional outcome at the final follow-up assessment were similar in the 2 groups. However, preoperative and postoperative CE angles and physeal inclination angles differed significantly in the treatment group (p < 0.05). The final epiphyseal valgus angles were better in the treatment group than in the control group (p = 0.05). The treatment group improved after the operation. Interpretation — Medial percutaneous epiphysiodesis performed through a mini-incision under fluoroscopic control is a worthwhile modality in terms of changing the valgus tilt of the femoral head.